2021
DOI: 10.1108/wje-12-2020-0645
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microhardness and wear properties of Al 6063 composite reinforced with yttrium oxide using stir casting process

Abstract: Purpose This study aims to analyse the changes in mechanical and wear performance of aluminium alloy when yttrium oxide particles are incorporated. The microstructures are studied to analyse the change in the grain structures. Worn surfaces are observed via scanning electron microscope to study the wear mechanism in detail. Design/methodology/approach Stir casting is used to incorporate varying composition of yttrium particles, having an average particle size of 25 micrometer, in aluminium alloy 6063 matrix.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Figure 6 shows how the hardness changes with the percentage of reinforcements. The findings of the current study are in line with those of more recent research (Bhoi et al , 2019; Bhoi et al , 2022; Butola et al , 2022).…”
Section: Resultssupporting
confidence: 93%
“…Figure 6 shows how the hardness changes with the percentage of reinforcements. The findings of the current study are in line with those of more recent research (Bhoi et al , 2019; Bhoi et al , 2022; Butola et al , 2022).…”
Section: Resultssupporting
confidence: 93%
“…7a, it is shown that all the CSP composites exhibited higher compressive strength than the neat and Fig. 7b reveals that the CSP composites' compressive strength is generally enhanced compared with the neat, even the least enhancement experienced by 15 wt% CSPs reinforced composite (132.54 MPa) is about 1.1% increment compared with the neat (131.10 MPa); which implies that voids are not closer to the testing surface (top) but lies deep within the composites [18]. The enhancement is attributed to the good bond between the Al 6063 matrix and the CSPs reinforcement, because SiC and CSPs may interact with the movement of dislocation of the matrix material thereby causing dislocation clamp down at matrix-particle contact [16,[45][46][47].…”
Section: Mechanical Properties Of the Neat And Crab Shell Particles R...mentioning
confidence: 87%
“…Because of its medium strength corrosion resistance and good surface finish, it is also referred to as the architectural alloy. 25,26 To study the significant effect of reinforcement and FSP the study was performed on three plates. Plate-1 or the base plate aliased (Al00).…”
Section: Methodsmentioning
confidence: 99%